Role of autofluorescence technique in detection of mycobacterial bacilli on fine needle aspiration cytology in tubercular lymphadenitis in comparison to conventional methods - Kumar, Sanjay; Gupta, Ritika; Kaushik, Nidhi; Kataria, Sant Prakash; Singh, Sunita (International Journal of Research in Medical Sciences, 2022)
Background: Lymphadenopathy is the most common presentation of extrapulmonary tuberculosis. Fine needle aspiration cytology (FNAC) has emerged an important role in the evaluation of peripheral adenopathy as a possible non-invasive procedure. Conventional Ziehl-Neelsen (ZN) method for acid fast bacilli (AFB) plays an important role in the diagnosis and the monitoring of treatment in tuberculosis. Fluorescence microscopy using auramine-rhodamine (AR) or Papanicolaou (PAP) staining has been considered superior to ZN staining. Methods: The study was conducted in tertiary care centre for a period of 2 years. A total number of 75 patients were included in the study. Four smears made from each aspirate: three air dried smears were stained with Giemsa, ZN, and AR stains and one was wet fixed for PAP stain for autofluorescence. Aspirate sent for culture over Lowenstein-Jensen medium was taken as a reference method. Results: Seventy five aspirates reported as tuberculous lymphadenitis on cytomorphology were stained with various methods. Autofluorescence was of more diagnostic utility for detection of AFB when cytologically only necrosis (64.71%) or granulomatous lymphadenitis (42.11%) was seen. With necrotising granulomatous lymphadenitis reported cases, Auramine Rhodamine was positive in maximum cases (66.7%) and was significant statistically. Overall taking culture as gold standard ZN stain was most specific (100%) and Auramine Rhodamine was most sensitive (82%). Conclusions: There is a definite advantage of autofluorescence in detecting mycobacteria over Ziehl-Neelsen and auramine rhodamine stain as it is more sensitive as well as an inexpensive technique. Autofluorescence can be a useful addition to routine cytology for early diagnosis and effective treatment.